Pertumbuhan dan Hasil Kedelai Edamame (Glycine max (L) Merill) Terhadap Pemberian Kombinasi Legin dan Kompos di Media Tailing Pasir Pasca Tambang Timah - Ardila Mughniyarti Dila; Rion Apriyadi; Riwan Kusmiadi (Fakultas Pertanian Universitas Majalengka, 2024)
Post tin mining land in Bangka Belitung can still be utilized as agricultural land with the application of various soil amandment including the combination of compost and legin. The compost provide organic matter for the soil and legin provide rhizobium to maximize nitrogen fixation in the soil. Post tin mining land improved with compost and legin combination can be used potentially for the development of edamame soybean commodities which are widely known as adaptive plant on suboptimal land. The purpose of this study was to determine the type of compost, legin dose and the best combination of both compost and legin on the growth and the yield of edamame soybeans in sand tailing media. This research had been conducted in February-August 2023 at the Experimental and Research Station, Faculty of Agriculture, Fisheries and Marine, Universitas Bangka Belitung. This study used a field experimental method with a Factorial Randomized Group Design with the first factor was the dose of legin, consists of 3 treatment levels, namely: L0: No treatment (Control), L1: 10 g legin, L2: 12 g legin. The second factor was the type of compost consisting of 3 treatment levels, namely: P1: Cow dung compost, P2: rice husk compost, P3: Commercial compost. There were 9 treatment combinations that were replicated 4 times. Each experimental unit had 6 plants so that 216 plant populations were obtained and 144 plants were obtained as samples. The results showed that the dose of 12 g legin had the highest effect on edamame growth and 10 g legin treatment had the highest effect on edamame yield. Commercial compost treatment had the best effect to edamame growth, while rice husk compost had the best effect to edamame yield. The combination of rice husk compost and 10 g legin was the treatment combination that showed the best growth and yield of edamame soybean plants in sand tailing media of post tin mining. Keywords: Edamame, rice husk, compost, legin, sand tailings